Chemical composition of the dufour gland secretion in queens of Melipona bicolor (Hymenoptera, Meliponini) - Abdalla, Fábio Camargo [UNESP]; Jones, Graeme R.; Morgan, David; Cruz-Landim, Carminda da [UNESP] (FapUNIFESP (SciELO), 2004)
We describe differences in the chemical composition of the Dufour gland secretion of virgin and physogastric queens of Melipona bicolor through gas chromatography and mass spectrometry. The Dufour gland secretion of virgin queens consists only of hydrocarbons, while that of physogastric queens contains, besides these, a variety of other compounds, such as isobutyrate and acetate esters. Such differences may indicate the queen fecundity condition and the oxygenated compounds of the physogastrics secretion may help to increase their attractiveness.
Keywords: Dufour gland; Ester; Hydrocarbon; Melipona bicolor; Pheromone; Physogastric queen; Stingless bee; acetic acid ester; hydrocarbon; isobutyric acid; chemical composition; female fertility; gas chromatography; Hymenoptera; mass spectrometry; secretion